2005
DOI: 10.1002/uog.1861
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted laparoscopic cryomyolysis: two‐ and three‐dimensional findings before, during and after treatment

Abstract: Objective To investigate the role of two-and threedimensional (2D and 3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Recently, less invasive surgical approaches and medical procedures have been developed, such as observation, gonadotropin-releasing hormone analogues and add-back therapy (gonadotropinreleasing hormone analogues plus estrogenprogestogen combination continuously), hysteroscopic resection of submucosal myomas, and laparoscopic myomectomy. 21,22 Other innovative conservative techniques are myolysis, cryomyolysis, 23,24 and uterine artery embolization. 21,22,25,26 When leaving the uterus and myomas in situ, it is important to first exclude LMS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, less invasive surgical approaches and medical procedures have been developed, such as observation, gonadotropin-releasing hormone analogues and add-back therapy (gonadotropinreleasing hormone analogues plus estrogenprogestogen combination continuously), hysteroscopic resection of submucosal myomas, and laparoscopic myomectomy. 21,22 Other innovative conservative techniques are myolysis, cryomyolysis, 23,24 and uterine artery embolization. 21,22,25,26 When leaving the uterus and myomas in situ, it is important to first exclude LMS.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, accurate preoperative imaging of myoma size, location and vascularization is crucial The best means by which such imaging is accomplished is by 3D power Doppler, that provides an accurate assessment of fibroid vascularization thereby permitting the identification of the areas of the fibroid that are more vascularized and therefore more vulnerable to cryotherapy. 38 Cryomyolysis is still an experimental procedure. The available published data are insufficient to evaluate the effectiveness and safety of the procedure, because only 3 series have been published, including our study (67-70).…”
Section: Cryomyolysismentioning
confidence: 99%
“…Exacoustos evaluated and compared the role of 2D and 3D ultrasound before, during and after laparoscopic cryomyolysis in 10 women with uterine fibroid. 38 The authors used a semi-quantitative assessment of blood flow at the level of the fibroid capsule and inside the tumor. This study found that both, 2D and 3D power Doppler ultrasound was useful to assess fibroid vascularization but 3D power Doppler were best to evaluate such an evaluation.…”
Section: Uterine Leiomyomas and Sarcomasmentioning
confidence: 99%